Arsenic in water from the Bystre Thrust-Sheet (Outer Carpathians, Poland): Geological and environmental implications - Aleksander-Kwaterczak, Urszula; Andrzejak, Jakub; Świerczewska, Anna; Lukaj, Konrad (Geology, Geophysics and Environment, 2024)
The article focuses on the physicochemical parameters of water in streams, springs, boreholes, and intakes from the Bystre Thrust-Sheet (the Silesian Nappe, Fore-Dukla Zone), the only area in the Polish segment of the Outer Carpathians where arsenic minerals occur. These waters are characterized by the presence of arsenic, lithium, mercury, barium, strontium and usually high CO2 concentrations. The study aimed to determine the range of the geochemical anomaly of arsenic in water. An important aspect was to determine the origin of As and link its presence with the content of ions of other chemical elements dissolved in water. The sampling points were designated based on geological maps with a particular emphasis on the occurrence of tectonic dislocations and the configuration of the river network. In the selected places 47 samples of water were taken, and various elements were determined. Then, the range of occurrence of various types of water that differed from the average concentrations of selected ions was analysed. The potential relationship between the chemical composition of water and the geology of the Bystre Thrust-Sheet was also discussed. The high concentrations of arsenic were found only in springs and boreholes. In flowing waters, these concentrations quickly decreased due to dilution or precipitation and binding with the solid phase. Relatively high (max. 378.72 μg/L) arsenic concentration, which significantly exceeded the permissible value (50 μg/L), was detected in the Bystre 1 borehole. This water has a pH value of 7.85 indicating its alkaline nature. When considering water use for health purposes, it is necessary to monitor its arsenic content. The conditions prevailing in waters, mainly high pH, favour the immobilization of metals in sediments and suspended matter. The lower concentrations of arsenic in flowing waters may be attributed to the strongly calcareous nature of the Cieszyn beds which act as a natural barrier, limiting the migration of arsenic beyond the Bystre Thrust-Sheet.